'Climate Refugees': An Oceanic Perspective. Issue 1 (12th January 2017) - Hingley, Rebecca
Abstract: The primary argument of this article seeks to highlight the irresponsible and insensitive categorisation of the Pacific peoples as 'climate refugees'. International actors' interpretation and use of such a term is damaging as it depicts these peoples as a vulnerable, rather than resilient group. The term effectively strips them of their agency and the potential for their valuable knowledge and efforts to contribute to the fight against a natural phenomenon that proves the most serious threat to humankind today, climate change. In the first section the international perception will be addressed, in the second section the Oceanic understanding will be explored in contrast, and finally in the third section, the implications for International Relations will be outlined. In conclusion, we find that the impact of the term 'climate refugees' is detrimental at both the conceptual and experiential level, making its deconstruction a complex but necessary task.